Characterization of soluble portions from cellulose, hemicellulose, and lignin methanolysis. (15th June 2019) - Yan, Hong-Lei; Li, Zhan-Ku; Wang, Zhi-Cai; Lei, Zhi-Ping; Ren, Shi-Biao; Pan, Chun-Xiu; Tian, Yu-Jiao; Kang, Shi-Gang; Yan, Jing-Chong; Shui, Heng-Fu
Highlights: Cellulose has the highest soluble portion (SP) yield, followed by hemicellulose and lignin. The SPs were detailedly analyzed with a GC/MS and FTICRMS. GC/MS analysis shows that compositions of the SPs are quite different. The most abundant class species in cellulose-, hemicellulose-, and lignin-derived SPs are O 5, O 5, and O 2, respectively. ADBE and OAN of O 4 - O 10 class species in the SPs have a negative correlation. Abstract: Methanolysis of the three biomass components was conducted to afford soluble portions (SPs) and residues. Cellulose has the highest SP yield, followed by hemicellulose and lignin. The relatively volatile or less polar species in the SPs were analyzed with a gas chromatograph/mass spectrometer (GC/MS) and the polar species were identified with a negative-ion electrospray ionization Fourier transform ion cyclotron resonance mass spectrometer (FTICRMS). According to analysis with GC/MS, sugars, esters, and phenols are the predominant compounds in cellulose- and hemicellulose-, and lignin-derived SPs, respectively. The analysis with FTICRMS shows that the molecular masses in the SPs range from 100 to 500 u and those in cellulose-/hemicellulose-derived SPs dominate from 250 to 300 u but in lignin-derived SP concentrates from 300 to 350 u . The identified compounds were assigned to O n class species with double bond equivalent (DBE) values of 1–14 and carbon atom numbers of 5–35. The most abundant class species in cellulose-, hemicellulose-, and lignin-derived SPs are O 5, O 5, and O 2, respectively. The van Krevelen diagrams of O n class species suggest that primary species in lignin-derived SP are mainly located in a relatively narrow region with atomic ratio of O/C 0.0–0.3 and atomic ratio of H/C 1.0–1.3, while those in cellulose- and hemicellulose-derived SPs are principally located in a wider region with atomic ratio of O/C 0.2–0.8 and atomic ratio of H/C 0.8–1.5. The oxygen atom numbers of O 4 − O 10 class species was negatively correlated with the average DBE value, which indicates a cyclic structure or double bond will be generated (opened or saturated) with the removal (addition) of oxygen atoms.